Chromosomal distribution of the transposable elements Osvaldo and blanco in original and colonizer populations of Drosophila buzzatii. - Garcia-Guerreiro, M.P.; Fontdevila, A. (Genetics research, 2001)
Chromosomal distribution of transposable elements (TEs) Osvaldo and blanco in D. buzzatii was studied in three original natural populations from Argentina (Berna, Puerto Tirol and La Nostalgia) and a colonizer population from the Iberian Peninsula (Carboneras). The Spanish population showed significant differences for Osvaldo and blanco copy numbers when we compared the X chromosome and the autosomes; but it is mainly the accumulation of copies in chromosome 2, where most sites with high insertion frequency were located, that causes the discrepancy with the negative selection model. We found no significant differences in TE frequency between chromosomal regions with different exchange rates, and no evident accumulation of TE was detected within chromosomal inversions where recombination rate is reduced. The Carboneras population shows euchromatic sites of Osvaldo and blanco with high occupancy and others with low copy number. On the contrary, Argentinian populations show only a generalized low occupancy per insertion site. Moreover, the mean copy number of both elements is higher in Spain than in Argentina. All these results suggest an important role of the colonization process in the distribution of TEs. The increase in the copy number of the TEs analysed and their elevated frequency in some chromosomal sites in Carboneras is, most probably, a sequel of the founder event and drift that took place at the time of the colonization of the Old World by D. buzzatii from the New World some 300 years ago.